1984
DOI: 10.1073/pnas.81.7.2060
|View full text |Cite
|
Sign up to set email alerts
|

On the mechanism of energy transduction in myosin subfragment 1.

Abstract: It is proposed that the myosin subfragment 1 moiety of the muscle contractile apparatus is a self-contained "engine" whose operational plan is based on the interactive nature of ATP (or degradation intermediate) binding and actin binding, made possible by an intersite communication system. It is suggested that the spatial information required for examining this engine can, at least provisionally, be derived from fluorescence resonance energy transfer measurements interpreted by the Forster equation and that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
65
0

Year Published

1987
1987
2001
2001

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 54 publications
(26 reference statements)
1
65
0
Order By: Relevance
“…The binding of the intermediates of the ATP cycle decreases the affinity of actin for its binding site and vice versa. Altogether, the results imply the existence of inter-site communication in S1 [13,141. On the basis of stability, the actin-S1 complexes can be resolved into three classes: (a) rigor complex, no occupant at the nucleotide site of S1, with highest stability; (b) strongly attached state, nucleotide-binding site of S1 is occupied by ADP, with intermediate stability; (c) weakly attached state, nucleotide site of Sl is occupied by ATP or ADP plus P,, with low stability.…”
mentioning
confidence: 52%
“…The binding of the intermediates of the ATP cycle decreases the affinity of actin for its binding site and vice versa. Altogether, the results imply the existence of inter-site communication in S1 [13,141. On the basis of stability, the actin-S1 complexes can be resolved into three classes: (a) rigor complex, no occupant at the nucleotide site of S1, with highest stability; (b) strongly attached state, nucleotide-binding site of S1 is occupied by ADP, with intermediate stability; (c) weakly attached state, nucleotide site of Sl is occupied by ATP or ADP plus P,, with low stability.…”
mentioning
confidence: 52%
“…Actin binding also produces structural changes in S l which affect ATP binding and hydrolysis. Thus, there is coupling between the two binding sites (Botts et al, 1984). It is, therefore, obvious that the characterization of the actin and ATP binding sites of S1 and of the conformational changes which take place in the S1 structure during the myosin -actin interaction, coupled with ATP hydrolysis, has a great significance.…”
mentioning
confidence: 99%
“…The 50-kDa fragment seems also to be involved in the nucleotide binding [24-261. Fluorescence resonance energy transfer measurements have shown that the nucleotide and actin binding sites are not within chemical reaction distance of each other, which suggests that the functionally important communication between these sites involves ligand-induced conformational changes [27]. Nucleotide-induced structural changes in the myosin head have been detected in a number of spectroscopic [28 -371, chemical modification [38 -421, and proteolytic digestion studies [43 -481 on myosin and its subfragments, heavy meromyosin and S1.…”
mentioning
confidence: 99%